ENHANCING PREOPERATIVE COMFORT: REDUCING HOSPITALIZATION ANXIETY IN CHILDREN WITH PUZZLE PLAY THERAPY FOR HYPOSPADIAS SURGERY - Wulandari, Aning Aprilia; Punjastuti, Budi (Himpunan Perawat Medikal Bedah Indonesia (HIPMEBI) Regional Jawa Barat, 2024)
Hypospadias is a congenital abnormality that can be defined as a urethral opening that is not in its proper place. In Indonesia, what confirms that hypospadias cases are high is that the number of cases is stable, neither increasing nor decreasing. According to data obtained from the Cendana 4 room register, there were 23 cases of children with hypospadias for the period January-April 2022. Most of these cases have been operated on. During treatment, children will experience anxiety. The purpose of this study was to describe puzzle play therapy to reduce anxiety at Dr. Sardjito Hospital, Yogyakarta. The descriptive method used is to provide a description that describes or uses assessment techniques, data collection, and reporting the results of the implementation carried out. After carrying out puzzle play therapy for 2 days with a frequency of 3 actions carried out within 15-20 minutes per meeting, the results obtained were that anxiety decreased from 25 (moderate anxiety) to 14 (mild anxiety). Providing play therapy can reduce hospitalization anxiety in children with pre-hypospadias surgery.